The gift of cancer : a miraculous journey to healing - Michaels, Brenda, frey50; Mercant, Marsha, 1953- (New York Skyhorse Publishing, 2014)
"For fourteen years, Brenda Michaels battled cancer. Then one day, she surrendered to the experience and found the gift in her disease. The Gift of Cancer speaks to anyone on a journey of well-being, whether suffering from a life-threatening disease or merely desiring to live a better, more fulfilling life. After Brenda's third cancer diagnosis and being told she had a year to live, she boldly stepped away from the accepted medical model, said no to chemotherapy, and chose alternative treatment. This unorthodox path, the connection of mind, body, and spirit, which many experts now believe is the key to true healing, ultimately saved Brenda's life and put her in control of her own destiny."--Page [4] of cover.
Journey to the past -- I married my father -- Diagnosis and recovery -- A familiar sadness -- Making other plans -- A heart and mind with separate lives -- Confronting reality -- Divine intervention -- Emotional rollercoaster -- Finding my voice -- Premonitions -- The face of betrayal -- Honoring my intuition -- Ready or not -- Cancer becomes my teacher -- The pupil learns -- Living in the present -- Loving myself back to health -- Letting go -- Moving into wellbeing -- Addendum: A lifelong guide to wellness.
Keywords: Michaels, Brenda; Cancer -- Patients -- United States; Cancer -- Alternative treatment